Estudio de prefactibilidad para la instalación de una planta de producción de suplemento proteico en polvo para consumo humano a base de soja (Glycine max) y maíz (Zea mays) - Pastrana Paredes, Leticia Zenaida (2021)
The main objective of this project is to demonstrate the technical, economic, financial and market viability, through a pre-feasibility study for the design and installation of a plant that produces a protein supplement in powder for human consumption based on soy (Glycine max) and corn (Zea mays) In the Market Study Chapter, the target market was identified, highlighting that the product would be accepted in the Modern Lima sector of Metropolitan Lima, which represents 12.7% of the population. With the aforementioned segmentation and the support of a survey conducted with 398 people, a project demand of 24,621.30 protein units of 1.22 kg corresponding to the first year will be presented. Then, a macro and micro location study was carried out in order to obtain the optimal location for the project. Thus, the departments of Lima, Amazonas and San Marin were first evaluated considering different factors, where Lima was chosen mainly because of its proximity to the target market. Finally, the plant will be located in Macropolis (Lurin), as it is the closest industrial zone to the market compared to the other alternatives evaluated. On the other hand, the size of the project plant was calculated from the analysis of various factors, obtaining a size of 37,817 units per year defined by the size - market relationship. Furthermore, a minimum of 11,758 units would have to be produced per year to make a profit. Regarding the engineering of the project, the drying operation represents the bottleneck of the process, with a capacity of 514,905 kg of protein. In addition, the plant layout was established, determining a total area of 540.95 m2. Regarding the economic and financial evaluation, it was demonstrated that the project is profitable, resulting in an economic NPV of S / 655,194.91, an IRR of 57.47% and a PR 2.85 years. In the same way, a financial NPV of S / 821,553.81 was obtained, IRR of 108.40% and a PR 1.59 years. Thus, for this project a total investment of S /. 584,798, of which 60% is financed at an effective annual rate of 17% and a COK of 22.98%. Finally, as a social evaluation, there is S / 27,847.53 of capital density, S / 0.11 of capital intensity and a product-capital ratio of S /. 9.05.